Vancouver Foot and Ankle WNS (Wound, Nerve, and Systemic) Classification System for Foot and Ankle Orthopedic Surgery. (September 2018) - Veljkovic, Andrea; Penner, Murray; Wing, Kevin; Abbas, Kaniza Zahra; Salat, Peter; Lau, Johnny; Femino, John E.; Phisitkul, Phinit; Amendola, Annunziato; Younger, Alastair
Background: Adverse events require consistent recording to determine the effect of alternate treatments. This study was undertaken to evaluate the Vancouver Foot and Ankle WNS complication scale to capture complications (W: wound, N: nerve, S: systemic) to assist in outcome recording. Methods: Interrater reliability was tested in 2 settings: (1) between 2 blinded clinicians in a live clinical setting and (2) between 8 orthopedic surgeons using case vignettes based on a retrospective analysis of 500 foot and ankle procedures performed at the Toronto Western Hospital, Department of Orthopaedics. The intrarater reliability of the WNS scale was tested in a single rater using the case vignettes. Inter- and intrarater reliability were assessed using the Fleiss and Cohen weighted kappa ( k ), respectively and 95% confidence intervals (CIs). There was adequate power over 0.8. Results: In the live clinical setting, the Cohen weighted k (95% CI) values for the W (0.935 [0.862, 1.01]), N (0.914 [0.752, 1.08]), and S (1 [1, 1]) parameters, indicating a near perfect level of agreement between raters. In the broader community of professional foot and ankle surgeons, the Fleiss k values (95% CI) had moderate agreement for the W (0.712 [0.688, 0.735]), N (0.775 [0.738, 0.811]), and high agreement for S (0.834 [0.802, 0.866]) parameters based on case vignettes. However, the Fleiss k values continued to indicate moderate to strong agreement between raters for all parameters. Conclusions: The WNS scale provided a standardized method of measuring foot and ankle surgical complications. There was at least moderate-strong interrater agreement for all parameters measured on case vignettes and excellent concordance in the live setting. Level of Evidence: Level III, comparative series.